The politics of dispossession in an Odishan steel town: $hChristian Strümpell - Strümpell, Christian (Contributions to Indian sociology, 2013)
The article discusses how industrial workers in Rourkela, a steel town in Odisha, experience the large-scale job losses entailed by the recent restructuring of ...
First published December 4, 2013
Gesehen am 09.10.2020